2020
DOI: 10.1590/1679-78255910
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Behavior of Exterior RC Beam-Column Joints Retrofitted using CFRP Sheets

Abstract: The seismic behavior of full-scale exterior reinforced concrete (RC) beam-column joints retrofitted with externally bonded Carbon Fiber Polymers (CFRP) is examined in this paper. Casting and testing of two similar reinforced concrete beam column connections in the absence of transverse reinforcement at the joints took place under opposing cyclic loading with regulated displacement so as to examine their fundamental seismic performance. The first joint was examined as the control specimen and the other specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…In study conducted by Laseima et al [49], the authors have been examined the seismic behavior of exterior RC-BCJs strengthened with CFRP. From the obtained results and compared to control specimens, the authors reported that the strengthened system improved by 62%, 209%, and 61.9% in terms of strength, energy dissipation, and ductility, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In study conducted by Laseima et al [49], the authors have been examined the seismic behavior of exterior RC-BCJs strengthened with CFRP. From the obtained results and compared to control specimens, the authors reported that the strengthened system improved by 62%, 209%, and 61.9% in terms of strength, energy dissipation, and ductility, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Pimanmas and chaimahawan [21] looked over into the beam-column junction specimens' shear strength and found that an expansion joint is an efficient way to lessen the amount of shear stress that is transmitted to the joint panel. Wide loops show that energy dissipation can also dramatically increase [22]. Brittle shear failure in beam joint is replaced by substantially ductile flexural failure.…”
Section: Introductionmentioning
confidence: 99%